2020
DOI: 10.1155/2020/7453406
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Molecular Mechanisms Underlying Sorafenib-Induced Hepatotoxicity

Abstract: Sorafenib is a small, orally-active multikinase inhibitor that is most frequently used for the management of renal cell carcinoma, hepatocellular carcinoma, and radioactive iodine-resistant thyroid carcinoma. However, recent reports have associated sorafenib with hepatotoxicity that can limit its clinical application, although the mechanism of hepatotoxicity is still to be elucidated. Thus, our study was designed to explore the molecular mechanisms underlying sorafenib-induced hepatotoxicity in an in vivo mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Immunoblot analysis was carried out as described previously [ 37 ]. Hepatic tissues were lysed, proteins were extracted, and equivalent amounts of proteins (0.02–0.05 mg) from control and treatment groups were loaded into 10–12% of SDS-PAGE for electrophoresis, followed by transfer to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis was carried out as described previously [ 37 ]. Hepatic tissues were lysed, proteins were extracted, and equivalent amounts of proteins (0.02–0.05 mg) from control and treatment groups were loaded into 10–12% of SDS-PAGE for electrophoresis, followed by transfer to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of sorafenib combination therapy with synthetic compounds showed a greater efficiency in reducing HCC and inducing apoptosis 6,8‐10 . The common mechanism of hepatotoxicity induction by chemotherapy and Sorafenib treatment is the enhancement of inflammation and oxidative stress which damages normal cells in liver 11,12 . A review article has highlighted the demand for combinational therapy for Sorafenib treatment which can increase the survival rate with minimized side effects 13 .…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] The common mechanism of hepatotoxicity induction by chemotherapy and Sorafenib treatment is the enhancement of inflammation and oxidative stress which damages normal cells in liver. 11,12 A review article has highlighted the demand for combinational therapy for Sorafenib treatment which can increase the survival rate with minimized side effects. 13 Combination with natural polyphenolic compounds has potentiated the anti-cancer effects of Sorafenib treatment on human liver cancer cell line.…”
mentioning
confidence: 99%
“…However, it has been demonstrated in some studies that one of the mechanisms of this toxicity may be associated with reactive oxygen species (ROS) generation [ 13 , 14 ]. It has been also confirmed that sorafenib used in chronic treatment induces liver toxicity by activation of oxidative stress [ 15 ]. Moreover, evidence exists that antioxidant enzymes such as catalase and glutathione peroxidase (GPX) have diminished activities in sorafenib-treated animals [ 15 ].…”
Section: Introductionmentioning
confidence: 96%
“…It has been also confirmed that sorafenib used in chronic treatment induces liver toxicity by activation of oxidative stress [ 15 ]. Moreover, evidence exists that antioxidant enzymes such as catalase and glutathione peroxidase (GPX) have diminished activities in sorafenib-treated animals [ 15 ]. All of these observations directly indicate that both sorafenib and lenvatinib are strongly involved in the oxidative processes in the cell.…”
Section: Introductionmentioning
confidence: 96%